2014
DOI: 10.1136/postgradmedj-2014-132681
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics of doctors who intend to follow clinical academic careers: UK national questionnaire surveys

Abstract: ObjectivesIt is well recognised that women are underrepresented in clinical academic posts. Our aim was to determine which of a number of characteristics—notably gender, but also ethnicity, possession of an intercalated degree, medical school attended, choice of specialty—were predictive of doctors’ intentions to follow clinical academic careers.DesignQuestionnaires to all UK-trained medical graduates of 2005 sent in 2006 and again in 2010, graduates of 2009 in 2010 and graduates of 2012 in 2013.ResultsAt the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…This research suggests that job-related factors, such as the level of support and satisfaction throughout the Foundation Programme impact on FP doctor career decision-making. 26–28 This information is important as it was previously assumed that medical careers preferences and values were formed prior to leaving medical school. 20 21 29 If this is not the case, it is crucial to identify the key attributes that play a crucial role in making training posts more attractive to those in the early stages of postgraduate training, as this intelligence may be used to inform interventions aimed at increasing the number of doctors staying in the training pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…This research suggests that job-related factors, such as the level of support and satisfaction throughout the Foundation Programme impact on FP doctor career decision-making. 26–28 This information is important as it was previously assumed that medical careers preferences and values were formed prior to leaving medical school. 20 21 29 If this is not the case, it is crucial to identify the key attributes that play a crucial role in making training posts more attractive to those in the early stages of postgraduate training, as this intelligence may be used to inform interventions aimed at increasing the number of doctors staying in the training pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Of our respondents, three quarters wanted to continue to a career in academia; this is consistent with previous research of interest in academia among early years trainees. 4,[27][28][29] A quarter of respondents had secured clinical academic fellowships following the AFP; interestingly however, 63% suggested that the AFP had no infl uence on their career decision, highlighting that other factors that the survey did not capture are playing a role. Greenberg et al have reported that factors such as participation in research and mentorship, which the AFP provides, play key roles in leading medical students into an academic career, but also considerations such as the amount of debt accumulated prior to medical school and professional aspects of academia play important roles.…”
Section: Discussionmentioning
confidence: 99%
“…Students' satisfaction was assessed using eleven items in Table 5 (1-11), whilst three items assessed their attention (12)(13)(14). Students enrolled in the iMSc in Clinical Anatomy were more satisfied with their programme than the students enrolled in the iBSc in Medical Science.…”
Section: Ibsc In Medical Science and Imsc In Clinical Anatomy Studentmentioning
confidence: 99%
“…With regard to assessing attention in Table 5, two out of three items (12)(13)(14) were in favour of the iMSc in Clinical Anatomy programme.…”
Section: Ibsc In Medical Science and Imsc In Clinical Anatomy Studentmentioning
confidence: 99%
See 1 more Smart Citation